Pengambangan Inovasi Produk Parfum Sepatu Yang Dijual Online Dan Offline Pada UKM “Cleds Pro” - Cellin Aulia; Desak Kade Shaila Indita; Grace Septiana Putri; Salman Alfarisi; Silahudin Silahudin; Fitri Komariyah (Trending: Jurnal Manajemen dan Ekonomi, 2025)
CledsPro is a business engaged in retail type, namely the development of shoe perfume product innovation. The development of shoe perfume innovation at “CledsPro” is expected to increase sales and expand market share, both in online and offline markets. By combining good quality shoes with a touch of attractive aroma, “CledsPro” SMEs can offer products that are unique and different from other competitors. This research method uses descriptive qualitative methods from 20 respondents. The purpose of this research is to find out how many people purchase shoe perfume products through online and offline and their aroma variants. Based on the results of the review, it was found that 60% of people made online product purchases and 40% of people made offline purchases and there were 75% of people who liked the Mercy variant and 25% of people who liked the Kiss variant. Strong coordination between marketing, production, and research and development teams has created a dynamic innovation ecosystem. A systematic approach to collecting and analyzing consumer feedback enables SMEs to continuously refine products according to market needs. An integrated marketing strategy between online and offline platforms has expanded the product's reach and appeal.